Intranasal administration of a single dose of MVA-based vaccine candidates against COVID-19 induced local and systemic immune responses and protects mice from a lethal SARS-CoV-2 infection - Pérez, Patricia; Astorgano, David; Albericio, Guillermo; Flores, Sara; Sánchez-Cordón, Pedro J.; Luczkowiak, Joanna; Delgado, Rafael; Casasnovas, José M.; Esteban, Mariano; García-Arriaza, Juan (Frontiers in Immunology, 2022)
Current COVID-19 vaccines are administered by intramuscular route, but this vaccine administration failed to prevent SARS-CoV-2 virus infection in the upper respiratory tract, mainly due to the absence of virus-specific mucosal immune responses. It is hypothesized that intranasal (IN) vaccination could induce both mucosal and systemic immune responses that blocked SARS-CoV-2 transmission and COVID-19 progression. Here, we evaluated in mice IN administration of three modified vaccinia virus Ankara (MVA)-based vaccine candidates expressing the SARS-CoV-2 spike (S) protein, either the full-length native S or a prefusion-stabilized [S(3P)] protein; SARS-CoV-2-specific immune responses and efficacy were determined after a single IN vaccine application. Results showed that in C57BL/6 mice MVA-based vaccine candidates elicited S-specific IgG and IgA antibodies in serum and bronchoalveolar lavages, respectively, and neutralizing antibodies against parental and SARS-CoV-2 variants of concern (VoC), being MVA-S(3P) the most immunogenic vaccine candidate. IN vaccine administration also induced polyfunctional S-specific Th1-skewed CD4+ and cytotoxic CD8+ T-cell immune responses locally (in lungs and bronchoalveolar lymph nodes) or systemically (in spleen). Remarkably, a single IN vaccine dose protected susceptible K18-hACE2 transgenic mice from morbidity and mortality caused by SARS-CoV-2 infection, being MVA-S(3P) the most effective candidate. Infectious SARS-CoV-2 viruses were undetectable in lungs and nasal washes, correlating with high titers of S-specific IgGs and neutralizing antibodies against parental SARS-CoV-2 and several VoC. Moreover, low histopathological lung lesions and low levels of pro-inflammatory cytokines in lungs and nasal washes were detected in vaccinated animals. These results demonstrated that a single IN inoculation of our MVA-based vaccine candidates induced potent immune responses, either locally or systemically, and protected animal models from COVID-19. These results also identified an effective vaccine administration route to induce mucosal immunity that should prevent SARS-CoV-2 host-to-host transmission.